Expressive Speech Acts on The Poem “Salamun ‘Alaikum Wa ‘Alainassalam” by Anis Syausyan (Pragmatic Study) (Jurnal Adabiya, 2023)
Abstract: Speech acts are part of a pragmatic analysis that examines language from the aspect of actual use. The text in this poem has a communication process and contains utterances that refer to speech acts. This study discusses the analysis of expressive speech acts in the text of the Assalam poem in terms of the types and functions of expressive speech acts in the text of the poem. The purpose of this research is to describe the expressive speech acts of Anis Syausyan in Assalam. This research uses a qualitative description research method. Collecting data in this study using observation techniques and note-taking techniques. The research data is in the form of fragments of Anis Syausyan's speech in the form of expressive speech acts. The source of the research data is the entire utterance contained in the Assalam poem. From this research it is hoped that expressive speech acts in poetry can be identified. The findings are explained as follows, the types of expressive speech acts contained in the poem "Assalam" consist of the first; speech act of criticizing, second; speech act of complaining, third; speech acts of praise, fourth; speech act of blaming, fifth; insulting speech act